2021
DOI: 10.1029/2020je006498
|View full text |Cite
|
Sign up to set email alerts
|

Autocorrelation of the Ground Vibrations Recorded by the SEIS‐InSight Seismometer on Mars

Abstract: ambient vibrations and seismic events are computed and validated by inter-comparison • The stability of autocorrelations at 2.4Hz resonance favor an excitation by a diffuse seismic wavefield • Various arrivals are observed in autocorrelation functions and interpreted as seismic reflections on internal discontinuities

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
43
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3
1
1

Relationship

2
3

Authors

Journals

citations
Cited by 40 publications
(48 citation statements)
references
References 47 publications
5
43
0
Order By: Relevance
“…Indeed, the 10.6 s signal is a likely candidate for a reflection from the base of the crust owing to its two-way travel time, negative polarity, strengths and robustness. En--19-manuscript submitted to ESS ergy at similar lag time has also been reported by Deng and Levander (2020) and Compaire et al (2021) and interpreted as P-wave Moho reflection. The 10.6 s signal seems to be consistent with models obtained for receiver functions from marsquake data (Lognonne et al, 2020;Knapmeyer-Endrun et al, 2021) This is based on the assumption that the crust-mantle boundary is stronger than a midcrust discontinuity.…”
Section: Discussionsupporting
confidence: 70%
See 4 more Smart Citations
“…Indeed, the 10.6 s signal is a likely candidate for a reflection from the base of the crust owing to its two-way travel time, negative polarity, strengths and robustness. En--19-manuscript submitted to ESS ergy at similar lag time has also been reported by Deng and Levander (2020) and Compaire et al (2021) and interpreted as P-wave Moho reflection. The 10.6 s signal seems to be consistent with models obtained for receiver functions from marsquake data (Lognonne et al, 2020;Knapmeyer-Endrun et al, 2021) This is based on the assumption that the crust-mantle boundary is stronger than a midcrust discontinuity.…”
Section: Discussionsupporting
confidence: 70%
“…All in all, they use data recorded during the evening hours for which autocorrelations have the highest signalto-noise ratio (SNR) and find a signal at 10.6 s and at 21 s which they interpret as reflections from crustal layers. They also show that glitches can not interfere with these reflections as they are separated by more than 30 s. The repeat time of donks, however, can be much smaller with maximum at about 10 s around 17-18 h LMST (Compaire et al, 2021). The authors argue that the observed stability of the 10.6 s signal with time -20-manuscript submitted to ESS is not correlated with the overall distribution of donks which finally makes a donk origin of these reflections unlikely.…”
Section: Discussionmentioning
confidence: 95%
See 3 more Smart Citations